Design and analysis of fuzzy PID controller with derivative filter for AGC in multi‐area interconnected power system. Issue 15 (1st November 2016) - Mohanty, Pradeep Kumar; Sahu, Binod Kumar; Pati, Tridipta Kumar; Panda, Sidhartha; Kar, Sanjeeb Kumar
Abstract : This study presents a comprehensive analytical study of a fuzzy proportional‐integral‐derivative (fuzzy‐PID) controller with derivative filter (fuzzy‐PIDF) for automatic generation control (AGC) in multi‐area power system tuned by a novel hybrid local unimodal sampling‐teaching learning based optimisation (LUS‐TLBO) algorithm. The relevant advantage of this recommended controller is its high sensitivity to load perturbation. Initially a two area non‐reheat type thermal system is considered and the gains of PIDF controller are tuned employing hybrid LUS‐TLBO algorithm. The supremacy of PIDF controller is shown by comparing the results with some recently published articles. The study is further extended to design fuzzy logic based PID controller with derivative filter (fuzzy‐PIDF) for AGC of the same power system employing hybrid LUS‐TLBO algorithm. Supremacy of the proposed approach is shown by comparing the results with another recently published article. In addition, the work is also extended to deal with AGC issues in two area multi source hydro thermal power system using the proposed controller. Finally, it is seen that fuzzy‐PIDF controller retains its supremacy over PID/PIDF/fuzzy‐PID controllers. In addition to it, robustness analysis is carried out for the non‐reheat two area thermal power systems by varying different parameters within the range of ±50%.